Building Spirituality from an Early Age in the Digital Era: Innovative Strategies for Islamic Religious Education - Elsa Anjar Martiana; Fajar Syarif; Ergun Yildirim (Indonesian Journal of Early Childhood Educational Research (IJECER), 2024)
The digital era has profoundly transformed early childhood education, creating both opportunities and challenges for Islamic Religious Education (PAI). Young children are increasingly exposed to digital media that influences their cognitive, emotional, and moral development from an early age. This condition requires innovative educational strategies that not only enhance religious knowledge but also foster spirituality, moral character, and ethical awareness rooted in Islamic values. This study employs a qualitative literature review approach, analyzing scholarly works published between 2018 and 2023 related to early childhood spirituality, Islamic education, digital literacy, and character education. The findings reveal that effective spiritual development in Islamic early childhood education requires an integrated framework that combines the internalization of aqidah, ibadah, and akhlaq with value-based digital literacy, child-centered pedagogy, and character-oriented curriculum design. Furthermore, the success of these strategies depends on strong collaboration among educators, families, and communities, as well as continuous formative evaluation. This study contributes a conceptual foundation for developing spiritually grounded, pedagogically innovative, and contextually responsive Islamic early childhood education in the digital era.